2018
DOI: 10.1542/peds.2017-2954
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Decision Support for Recognition and Management of Hypertension: A Randomized Trial

Abstract: The CDS had a significant, beneficial effect on the recognition of hypertension, with a moderate increase in guideline-adherent management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 18 publications
2
62
0
Order By: Relevance
“…Yet ASD cannot be diagnosed in infants, and there is no clear predictor of ASD in infants. Given that ~20% (Ozonoff et al, 2011) and 30% (Charman et al, 2017) of younger siblings of children with ASD, respectively, will receive a diagnosis of ASD or meet criteria for other developmental disruptions by 36 months of age, a public health approach to detecting ASD risk and monitoring at-risk children is needed (e.g. pre-term infants; Darcy-Mahoney et al, 2016).…”
Section: When To Start Intervention?mentioning
confidence: 99%
“…Yet ASD cannot be diagnosed in infants, and there is no clear predictor of ASD in infants. Given that ~20% (Ozonoff et al, 2011) and 30% (Charman et al, 2017) of younger siblings of children with ASD, respectively, will receive a diagnosis of ASD or meet criteria for other developmental disruptions by 36 months of age, a public health approach to detecting ASD risk and monitoring at-risk children is needed (e.g. pre-term infants; Darcy-Mahoney et al, 2016).…”
Section: When To Start Intervention?mentioning
confidence: 99%
“…Initiatives to improve recognition of HTN in the outpatient setting have included improved clinical decision support built into the EMR, and use of screening tables to provide more concise age‐ and sex‐based norms for pediatric BP, thus limiting the need to consult the more comprehensive tables that include height‐based thresholds. Both approaches have promise based on published studies, but even with the effective use of these tools, elevated BP remains commonly under‐recognized 20‐23 . In the inpatient setting, an EMR‐based intervention, especially one that calculates patient‐specific thresholds for appropriate BP based on admission height, age, and sex, could effectively warn staff of a BP elevation at the moment recognition is needed (when inputting a BP into the patient’s vitals record).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is worth noting that in a series of randomized trials, Priorities Wizard has been shown to improve BP control, glucose control, smoking cessation, and cardiovascular risk, reduce clinical inertia, and improve recognition and diagnosis of diabetes in those who meet clinical criteria for the disease. [16][17][18][19][20] Moreover, a formal cost-effectiveness analysis shows a base-case estimate of $3017 per quality adjusted life year gained, and the CDS system is likely to be cost saving to payers at scale. 21 Should Diabetes CDS Stand Alone, or Be Integrated with CDS for Other Conditions?…”
Section: Priorities Wizard: a Current Diabetes Clinical Decision Suppmentioning
confidence: 99%